Association Between 2010 Medicare Reforms and Utilization of Postacute Inpatient Rehabilitation in Ischemic Stroke. (July 2021) - Ifejika, Nneka L.; Vahidy, Farhaan; Reeves, Mathew; Xian, Ying; Liang, Li; Matsouaka, Roland; Fonarow, Gregg C.; Savitz, Sean I.
Abstract : Objective: The aim of the study was to investigate whether the elimination of trial admissions and the initiation of documentation requirements, via the 2010 Centers for Medicare and Medicaid Services Inpatient Rehabilitation Facility Prospective Payment System Rule, limited inpatient rehabilitation facility access while increasing skilled nursing facility utilization compared with home discharge in ischemic stroke patients. Design: This is a retrospective observational study using Get with the Guidelines – Stroke hospital data between January 1, 2008 and December 31, 2015 ( N = 1, 643, 553). Results: Between January 1, 2008 and December 31, 2009, 54.1% of patients went home, 25.4% to inpatient rehabilitation facility and 20.5% to skilled nursing facility. Between January 1, 2010 and December 31, 2015, there was a 1.4% absolute increase in home discharge, a 1.1% inpatient rehabilitation facility decline and a 0.3% skilled nursing facility decline. Within the 1.1% absolute decline in inpatient rehabilitation facility discharge, the adjusted odds of inpatient rehabilitation facility versus home discharge decreased 12% after 2010 Rule (adjusted odds ratio = 0.88, 95% confidence interval = 0.87–0.89, P < 0.0001). There was no statistically significant change in skilled nursing facility versus home discharge. Lower adjusted odds of inpatient rehabilitation facility discharge versus home discharge were identical across age groups and were present in all geographic regions. Conclusions: In populations with ischemic stroke, the Centers for Medicare and Medicaid Services 2010 Inpatient Rehabilitation Facility Prospective Payment System Rule was associated with a 1.1% absolute decrease in inpatient rehabilitation facility discharge, with a concomitant increase in home discharge rather than to skilled nursing facility. Abstract : Supplemental digital content is available in the text.